Analisis Kepuasan Pelanggan di Apotek Bunda Cikembar - Nida Salma Fahriani; Intan Rike Febriyanti (Pusat Riset dan Inovasi Nasional, 2022)
Apotek Bunda operates in a crowded environment or is in a supermarket area. This pharmacy has been established since 2016. This study aims to determine customer satisfaction when shopping at Apotek Bunda. The approach used in this research is qualitative-descriptive. Data collection techniques were carried out through interviews with seven informants who were regular customers or had shopped more than ten times at this pharmacy. The interview questions asked are about seven indicators of customer satisfaction. The results showed that of the seven indicators of customer satisfaction, only three indicators were met, namely product, price, and location. Meanwhile, promotion indicators, employee services, facilities, and atmosphere still need to be improved.